Correlation between Very Low-Density Lipoprotein and Trygliseride with Glycated Hemoglobin Levels in Type 2 Diabetes Mellitus Patients - Sherly Karolina Simanjuntak; I Nyoman Wande; Ida Ayu Putri Wirawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Patients with Type 2 Diabetes Mellitus (T2DM) have an increased prevalence of dyslipidemia, which contributes to a higher risk of dyslipidemia- related complications in T2DM such as cardiovascular disease and stroke. This study aimed to determine the correlation between TG and VLDL-C towards HbA1c levels in a person with T2DM. A retrospective study of 74 outpatients with T2DM at Sanglah General Hospital, Denpasar, who examined serum HbA1c and lipid profiles were traced for serum TG. From the obtained TG profile, a secondary calculation of VLDL was carried out using the Friedewald equation (TG/5). A correlation test was used to determine the relationship between TG and VLDL-C towards HbA1c levels. Serum TG (212.95±147.46 mg/dL) and VLDL (36.69±23.54 mg/dL) were found to be higher in the group with poor glycemic control (HbA1c > 7 mg/dL) compared to serum TG (111.00±39.56 mg/dL) and VLDL (21.05±6.13 mg/dL) in the group with good glycemic control (HbA1c â‰¤ 7 mg/dL) (p < 0.05). A positive correlation between serum TG (r=0.512; p < 0.001) and VLDL (r=0.18; p <0.001) towards HbA1c levels in T2DM patient was found. Insulin resistance increases the production of VLDL and ApoC-III in the liver and increased chylomicron absorption in the gastrointestinal tract, causing prolonged post-prandial lipemia and disruption of VLDL and TG clearance, thereby resulting in increased TG and VLDL in circulation. There is a significant positive correlation between serum TG and VLDL towards HbA1c levels in a patient with T2DM.